Periphyton-based apparatus for improving aquaculture production and method preparing thereof. - Md Yusoff, Fatimah; Mohamed Din, Mohamed Shariff; Mohamed, Suhaila; Kuppan, Perumal (2006)

(untitled)
A method to manufacture an apparatus for aquaculture improvement comprises the steps of providing at least one suitable construct into purified periphyton culture; growing a purified periphyton on the surface of a suitable construct until its surface coated with the periphyton; and removing the coated construct from the culture container for use. The construct is for use to improve water quality and increase growth and survival of aquatic organisms in aquaculture systems.